Meningkatkan pengetahuan sains pada anak melalui pendekatan eksplorasi lingkungan dengan bercocok tanam sayur di PAUD Al-Fattah Kota Bengkulu - Intan Tiara Shoti; Rita Prima Bendriyanti; Dwi Nomi Pura (Early Childhood Research and Practice, 2021)
This study aims to: Determine whether an environmental exploration approach with vegetable farming can improve children's science knowledge in PAUD Al-Fattah, Bengkulu City. The design applied in this study is Classroom Action Research (CAR) which is an approach to solving educational problems that aims to improve learning situations in the classroom. The subjects of this study were 16 students. Based on the results of the assessment through several stages of action, the percentage value of the first cycle of meeting I was 43% with the Start Developing (MB) assessment category, then increased to 56% in the first cycle of the second meeting with the Developing Appropriate (BSH) assessment category. In the second cycle of the first meeting there was an increase in the percentage value to 73% with the Developing according to Expectations (BSH) assessment category and in the second cycle of the second meeting the percentage value increased significantly by 95% with the Very Well Developed (BSB) assessment category. This means that through an environmental exploration approach by growing vegetables can improve children's science knowledge in PAUD Al-Fattah, Bengkulu City.